2020
DOI: 10.1155/2020/4357017
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Closure of Patent Ductus Arteriosus under Echocardiography Guidance: A Randomized Controlled Noninferiority Trial

Abstract: Background. Percutaneous occlusion under fluoroscopy guidance has become the preferred method for the treatment of patent ductus arteriosus (PDA). To avoid radiation exposure and contrast agent use, PDA occlusion under transthoracic echocardiography (TTE) guidance was conducted. Objectives. We assessed the hypothesis that the success rate of percutaneous PDA occlusion under TTE was noninferior to that under fluoroscopy guidance. Methods. In this single-center trial, 100 patients were randomly assigned in a 1 :… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…In general, normal fetuses are functionally closed within 10-15 hours of birth by contraction of the smooth muscle in the medial layer of the ductus arteriosus wall and permanently closed within 2-3 weeks of birth by formation of wrinkles in the endothelium of the ductus arteriosus and fibrosis of the subintimal connective tissue [15][16][17][18]. If PDA occurs, it will influence the body's hemodynamics, mainly because part of the aortic blood shunts through the PDA to the pulmonary artery, and then the shunt to the pulmonary artery blood flow and the right heart system blood flow, together entering the left atrium and left ventricle again through the pulmonary circulation, increasing the left ventricular volume load [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In general, normal fetuses are functionally closed within 10-15 hours of birth by contraction of the smooth muscle in the medial layer of the ductus arteriosus wall and permanently closed within 2-3 weeks of birth by formation of wrinkles in the endothelium of the ductus arteriosus and fibrosis of the subintimal connective tissue [15][16][17][18]. If PDA occurs, it will influence the body's hemodynamics, mainly because part of the aortic blood shunts through the PDA to the pulmonary artery, and then the shunt to the pulmonary artery blood flow and the right heart system blood flow, together entering the left atrium and left ventricle again through the pulmonary circulation, increasing the left ventricular volume load [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that the use of TTE reduced the procedure time, eliminated the need for femoral arterial access, and avoided the use of contrast agents. It also minimized radiation exposure, benefiting both patients and operators without compromising the effectiveness of defect closure, as supported by scientific literature (11)(12)(13) . TTE has also been successfully used for interventricular and atrial septal defects with the same objective of reducing radiation doses and decreasing the need for angiographies (16,17) .…”
Section: Discussionmentioning
confidence: 84%
“…This method successfully occludes PDA through femoral vein without using contrast agents and X-ray. In addition, there are no severe complications indicating the safety and effectiveness of this technique [ 14 ]. However, this technique also has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the largest cohort which explores the safety and effectiveness of transcatheter femoral vein occlusion of PDA under TEE guidance in children. In our center, the longest surgical time at the initial stage was 2 h, and the shortest time was 20 min with an average duration of 40.2 min, which indicates that this method represents a better alternative than other methods considering the learning curve [ 14 ]. However, it is also noteworthy that cases with surgical time longer than 2 h possibly need to be changed to open surgery to avoid the increased risks due to the prolonged operation.…”
Section: Discussionmentioning
confidence: 99%